Effects of increasing temperatures on methane concentrations and methanogenesis during experimental incubation of sediments from oligotrophic and mesotrophic lakes. Issue 5 (28th May 2016) - Fuchs, Andrea; Lyautey, Emilie; Montuelle, Bernard; Casper, Peter
Abstract: Global warming is expected to raise temperatures in freshwater lakes, which have been acknowledged to contribute up to 10% of the atmospheric methane concentrations. Increasing temperature enhances methane production and oxidation rates, but few studies have considered the balance between both processes at experimentally higher temperatures within lake sediments. The temperature dependence of methane concentrations, methane production rates, and methanogenic ( mcrA ) and methanotrophic ( pmoA ) community size was investigated in intact sediment cores incubated with aerobic hypolimnion water at 4, 8, and 12°C over 3 weeks. Sediment cores of 25 cm length were collected at two temperate lakes—Lake Stechlin (Germany; mesotrophic‐oligotrophic, maximum depth 69.5 m) and Lake Geneva (France/Switzerland; mesotrophic, maximum depth 310 m). While methane production rates in Lake Stechlin sediments did not change with increasing temperatures, methane concentrations decreased significantly. In contrast, methane production rates increased in 20–25 cm in Lake Geneva sediments with increasing temperatures, but methane concentrations did not differ. Real‐time PCR demonstrated the methanogenic and methanotrophic community size remained stable independently of the incubation temperature. Methane concentrations as well as community sizes were 1–2 orders of magnitude higher in Lake Stechlin than in Lake Geneva, while potential methane production rates after 24 h were similar in both lakes, with on average 2.5 and 1.9 nmol g −1 DW h −1, respectively. Our results suggest that at higher temperatures methane oxidation could balance, and even exceed, methane production. This suggests that anaerobic methane oxidation could be involved in the methane balance at a more important rate than previously anticipated. Key Points: Temperature affects methane production and oxidation in sediments Resulting methane concentration did not increase with temperature Community sizes of methanogens and methanotrophs did not change with temperature